Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. - Phan Cự Đệ,; Bùi Việt Thắng,; Hà Văn Đức,; Lý Hoài Thu,; Hồ Thu Giang,; Nguyễn Thị Hương Giang, (Văn học, 2004)
Vũ Bằng; Ngô Ngọc Bội; Triệu Bôn; Nguyễn Văn Bổng; Xuân Cang; Nam Cao; Đỗ Chu.